2022-RA-1483-ESGO Cytoreductive surgery in advanced ovarian cancer patients. (20th October 2022) - Yakovleva, Maria; Smirnova, Olga; Lavrinovich, Olga; Mikaya, Nikolay; Trifanov, Yuri; Urmancheeva, Adel; Berlev, Igor
Abstract : Introduction/Background: To determine the selection criteria for cytoreductive surgery in the advanced ovarian cancer patients Methodology: A cohort of 190 consecutive primary IIB-IV stage ovarian cancer patients underwent surgical treatment (including diagnostic laparoscopy) from august 2017 to august 2020. Assessment of the peritoneal carcinomatosis index (PCI) was according to P. Sugarbaker. The outcome of cytoreductive surgery was: complete – without a macroscopically detectable tumor, optimal – residual tumor ≤ 1 cm, non-optimal – residual tumor ≥ 1 cm Results: The complete and optimal cytoreduction achieved in 72.6% (138/190), suboptimal in 22% (42/190), 5% (10/190) only a diagnostic laparoscopy. PCI value ranged from 0 to 35 points. The median PCI in the group of optimal cytoreductions was 3 points (2; 6), non-optimal 19.5 points (15; 23). The optimal cut-off PCI point was 9.5 points (sensitivity=92.1%, specificity=86.2%, overall accuracy 87.4%). The main cause of non-optimal interventions (n=52) were: diffuse carcinomatosis of the small intestine and its mesentery – 73% (38/52), carcinomatosis of the hepatoduodenal zone – 9% (5/52) and a total of 16% (9/52) were other non-resectable tumors. Radiation diagnostic and intraoperative revision were comparable in 60.5% (115/190). The sensitivity of CT in detecting of the small intestine lesions was 23.7%, the specificity was 90%, while for laparoscopy – the sensitivity was 93.3%, and the specificity was 100%. In assessing of carcinomatosis of the hepatoduodenal zone, the advantage belongs to radiation diagnostic Methods the sensitivity of CT was 66.7%, the specificity was 97%, while the sensitivity of diagnostic laparoscopy was 0%. Conclusion: The threshold value for performing complete or optimal cytoduction is PCI = 9 points. The leading reasons for suboptimal cytoreductive operations were diffuse carcinomatosis of the small intestine wall and the mesentery. Diagnostic laparoscopy reduces the frequency of suboptimal cytoreductive operations from 67% to 13%.